2008
DOI: 10.1111/j.1469-8137.2008.02539.x
|View full text |Cite
|
Sign up to set email alerts
|

The sugar porter gene family of Laccaria bicolor: function in ectomycorrhizal symbiosis and soil‐growing hyphae

Abstract: Summary Formation of ectomycorrhizas, a symbiosis with fine roots of woody plants, is one way for soil fungi to overcome carbohydrate limitation in forest ecosystems. Fifteen potential hexose transporter proteins, of which 10 group within three clusters, are encoded in the genome of the ectomycorrhizal model fungus Laccaria bicolor. For 14 of them, transcripts were detectable. When grown in liquid culture, carbon starvation resulted in at least twofold higher transcript abundances for seven genes. Temporaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 55 publications
7
26
0
Order By: Relevance
“…Filamentous fungal transporters appear to hold diverse functional roles notably in plant-fungi symbiosis [55-57] pathogenicity [58,59], and ethanol production and tolerance [48,50,60-62]. In regards to tolerance, transcriptional studies have identified alcohol responsive genes associated with sugar transport [50,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous fungal transporters appear to hold diverse functional roles notably in plant-fungi symbiosis [55-57] pathogenicity [58,59], and ethanol production and tolerance [48,50,60-62]. In regards to tolerance, transcriptional studies have identified alcohol responsive genes associated with sugar transport [50,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…AMFs improve the host plants' absorption of water and nutrients from the soil; in return, 20% of the carbon that the plants fixed on their own is transferred to the fungi [12,13]. If carbon acquired from the plant is reduced, N may have a negative impact on arbuscular mycorrhizae (AM) abundance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mycorrhizal fungi participate actively to plant development (Smith and Read, 2008) by improvement of access to nutrients, particularly when resources become scarce. In turn, vegetal partners provide up to 20–25% of photosynthetic carbohydrates to their symbionts (López et al, 2008). The improvement of plant nutrition through mycorrhizal symbioses and the molecular bases of nutrient transfer are currently well studied for phosphorus (Javot et al, 2007; Plassard and Dell, 2010) and nitrogen (Müller et al, 2007; Jin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%